PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA DITINJAU DARI UNDANG-UNDANG KETENAGAKERJAAN NOMOR 13 TAHUN 2003 - Purnamasari, Dewi; Nur Hakim; Marni Emmy Mustofa (Journal of Innovation Research and Knowledge, 2025)
The research objectives of this thesis are: 1). To analyze how the rules of legal consequences for employers for violations of the rights of Domestic Workers. 2). To find out the legal protection of violations of the rights of Domestic Workers committed by employers. The method used in this study is normative juridical by conducting library research on primary, secondary and tertiary legal sources. The author's research approach uses a legislative, conceptual, analytical, case and historical approach. The data collection technique is carried out by library research, namely by collecting literature data such as books, journals, and results of research on legislation. The research results of this thesis are: 1) Legal consequences for employers for violations of Domestic Workers' rights The relationship between employers and Domestic Workers that Permenaker RI Number 2 Year 2015 has indeed regulated the rights and obligations of both domestic workers and employers is relatively balanced. However, in practice, this regulation is not widely known by the public and is not effectively implemented. This is due to low socialization and weak government supervision. Domestic workers are vulnerable to exploitation and violence. The case of Siti Khotimah in South Jakarta shows the real condition of how weak protection for domestic workers is. Although there are regulations that protect domestic workers, the absence of a specific law and the limited use of the TPKS Law in prosecutions make legal protection for domestic workers very inadequate. The cruel treatment of the victim shows that unprofessional and familybased working relationships can open the door to extreme violence and human rights violations. 2)Legal protection against violations of Domestic Workers' rights by employers The law for Domestic Workers (DWs) has actually been implied even though legal protection for DWs in Indonesia still has many weaknesses, but there are various regulations that can be used as a basis for imposing sanctions on employers who violate DWs' rights. These sanctions can be in the form of criminal, civil, administrative, and social sanctions. To strengthen legal protection for domestic workers, it is necessary to ratify the PPRT Bill with the presence of this law to provide legal certainty, establish protection, and guarantee the basic rights of domestic workers as informal workers.